The Effect of Arak Bali Administration on Spermatogenic Cell Counts in Wistar Rats: A Preliminary Study - Stephanus Rahardian Hersacra Nudu; I Gusti Ngurah Pramesemara; I Made Oka Negara; I Gusti Ayu Dewi Ratnayanti (Indonesian Andrology and Biomedical Journal, 2025)
Background: Male infertility is widely recognized as major health problem, contributing to around 50% infertility cases. Chronic excessive alcohol consumption has been found to negatively affect sperm quality. Arak Bali, a traditional spirit from Indonesia, is widely consumed, yet its specific impact on the process of spermatogenesis remains scientifically uninvestigated. Objective: This study aimed to evaluate the effects of chronic Arak Bali administration on the counts of spermatogonia, primary spermatocytes, and spermatids in male Wistar rats. Methods: This study utilized a post-test only control group design. Fourteen male Wistar rats were analyzed, allocated into a Control group (n=6) which received aquades, and an Intervention group (n=8) which was administered Arak Bali (40% v/v) daily for 42 days. For each rat, the average cell count from three seminiferous tubules was used as the representative value. Group data were compared using an independent T-test, with significance set at p < 0.05. Results: Spermatogonia, primary spermatocytes, and spermatids showing no statistically significant differences between the Control and Intervention groups for the mean counts of spermatogonia (p = 0.162), primary spermatocytes (p =0.571), or spermatids (p = 0.628). Conclusion: Chronic administration of 40% v/v Arak Bali at 0.5mL per rat per day did not significantly show a reduction in cell counts in spermatogonium, primary spermatocytes, and spermatid in Wistar rats.